What matters most to patients following percutaneous coronary interventions? A new patient-reported outcome measure developed using Rasch analysis - Soh, S.E.; Barker, A.L.; Ayton, D.R.; Ahern, S.; Morello, R.; Lefkovits, J.; Brennan, A.L.; Evans, S.; Zalcberg, J.R.; Reid, Christopher; McNeil, J.J. (PUBLIC LIBRARY SCIENCE, 2019)
© 2019 Soh et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.